Improvements in National Code Red transfusion practice in Scotland after adoption of recommendations from the Scottish National Code Red 2015 review. Issue 4 (April 2020) - Reed, Matthew J; Cooke, Claire; McMahon, Niall; Hands, Katherine; Henderson, Susan; Knight, Eleanor; Littlewood, Nicola; Latif, Munsoor; Tod, Naomi; McGarvey, Margaret; Hughes, Neil; Donald, Michael; et al.
Highlights: Interventions have improved code red transfusion practice in Scotland between 2013–15 and 2015–17. Pre-hospital clinicians are activating code red earlier giving the hospital more time to prepare transfusion components. 93% of code red patients received blood components with a 300% increase in pre-hospital transfusion (48 patients versus 16). CRC:FFP ratios are now below 2:1, previously not achieved until 150 min helped by introducing pre-thawed FFP into the ED resuscitation room. Introduction of Point-of-Care viscoelastic coagulation testing has led to more patients receiving these tests (12 versus none in 2013–2015). Abstract: Aims: The Scottish Transfusion and Laboratory Support in Trauma Group (TLSTG) previously reviewed all National Code Red activations between June 1st 2013 and October 31st 2015, generating a number of recommendations to be adopted to optimise the transfusion support given to patients following major trauma in Scotland. A repeat National survey was undertaken for all patients for whom Code Red was activated between 1st November 2015 and 31st December 2017. Methods: A clinical and transfusion lead for each centre entered anonymised data onto a secure electronic database (REDCap). Results: During the study period there were 66 activations (24 South-East of Scotland, 32 West, 10 East). Mean age was 45 years and 88% were male. Mean Injury Severity Score (ISS) was 28 with 75% blunt trauma. 93% (62/66) of Code Red patients received blood components with a 300% increase in pre-hospital transfusion (48 vs 16 patients; p <0.001). Median time from 999 call to Code Red activation reduced significantly to 37 min from 70 min ( p  = 0.01) giving the hospital more time to prepare transfusion components. 78% patients received pre-hospital tranexamic acid (TXA; improved from 70%, p  = 0.67, ns). Concentrated Red Cell (CRC): Fresh Frozen Plasma (FFP) ratio was always less than 2:1 and below 1.4:1 at 90 min, compared to 2013–15 when CRC: FFP ratios did not drop to below 2:1 until 150 min after arrival in the ED. Mean time for Full Blood Count (FBC; 46 mins versus 81; p  = 0.004) and clotting (53 mins versus 119; p <0.001) result was reduced. Survival to hospital discharge was unchanged (66% versus 63%; p  = 1.00 ns). Conclusions: Code Red practice has improved in several ways since our last survey with earlier Code Red activation, more patients receiving pre-hospital transfusion and improved CRC:FFP ratios. Interventions such as earlier on scene Code Red activation, provision of pre-hospital TXA, Emergency Department (ED) resuscitation room pre-thawed FFP and point-of-care viscoelastic coagulation testing have all contributed to these improvements in transfusion practice in Scotland.